2014
DOI: 10.1007/s13187-014-0685-z
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Cervical Cancer Screening, Diagnosis, and Enrollment in Medicaid: Experiences of Georgia’s Women’s Health Medicaid Program Enrollees

Abstract: Although cervical cancer incidence and mortality rates have declined in the USA, African American women have a higher incidence rate of cervical cancer and a higher percentage of late-stage diagnosis than white women. Previous analyses by the authors showed that, even after adjusting for age, provider location, and availability, African American women were almost half as likely as white women to be diagnosed or enter Medicaid while at an early stage of their cervical cancer. To understand why these differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…On balance, racial and–ethnic minorities and women of lower socioeconomic status were less likely to have a good understanding of prenatal testing options and of their own experience. These data parallel reports documenting disparities in various screening domains 15-19 . While the American College of Obstetricians and Gynecologists recommends that “...screening and invasive diagnostic testing for aneuploidy should be available to all women...regardless of maternal age” 20 , it appears that this information is not being effectively provided to all women, and that many do not understand the messages conveyed.…”
Section: Discussionsupporting
confidence: 83%
“…On balance, racial and–ethnic minorities and women of lower socioeconomic status were less likely to have a good understanding of prenatal testing options and of their own experience. These data parallel reports documenting disparities in various screening domains 15-19 . While the American College of Obstetricians and Gynecologists recommends that “...screening and invasive diagnostic testing for aneuploidy should be available to all women...regardless of maternal age” 20 , it appears that this information is not being effectively provided to all women, and that many do not understand the messages conveyed.…”
Section: Discussionsupporting
confidence: 83%
“…Of the Turkish students, 78.9% knew about early diagnosis of cervical cancer, 66.3% knew about the recommendation of the Pap smear test, 14.2% knew about the HPV vaccine, and 25.3% knew about safe sexual practice. Of the Polish students, 68.8% knew about early diagnosis of cervical cancer, 41.9% knew about the Pap smear test, 20% knew about the HPV vaccine, and 15.6% knew about safe sexual practice.…”
Section: Resultsmentioning
confidence: 99%
“…The Papanicolaou test (Pap smear), which is systematically used in the fight against cervical cancer, is an effective, low-cost, and highly sensitive early diagnostic method which is easy to apply and reduces the burden of the treatment, morbidity and mortality (2,11,12). Cervical cancer shows the benefit of early diagnosis best; developed countries report that invasive cervical cancer rates have been reduced with the use of routine Pap smear screening tests over the last 40-50 years (7,(13)(14)(15).…”
mentioning
confidence: 99%
“…Early diagnosis and treatment need to raise awareness about the risk factors, symptoms, prevention, and screening of gynecologic cancers 5,6,21,35 . Cooper et al 36 reported that a majority of women had heard of cervical, ovarian, and endometrial cancers, but not vaginal and vulval cancers.…”
Section: Discussionmentioning
confidence: 99%